From local to global: The role of knowledge, transfer, and capacity building for successful energy transitions - Hanno Michel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2020)
Germany has set the challenging goal of reducing its greenhouse gas emissions by 40 percent by the year 2020 as compared to 1990 (BMUB 2014). This German Energiewende (energy transition) has led to significant changes in the electricity sector, such as a continuously increasing percentage of renewable energies, supported by corresponding governance and political efforts. However, despite these political and economic efforts, the 2020 goal will most likely only be reached due to the tremendous unplanned effects of the COVID-19 pandemic on energy usage for transport and mobility (Agora Energiewende 2020). In addition to technological advances, a change in individual and collective behavior seems highly necessary to achieve future transition goals. The aim of this discussion paper is to summarize the state of research on how people's behavior in the context of climate change and energy transitions is shaped, and to put forward potential avenues for further research and action. The paper departs at a local level by looking at factors that guide citizens' individual energy-related actions and thus impact their energy-saving behavior. Knowledge about climate change and energy is generally believed to influence a person's energyrelated behavior, although its measured effects vary significantly in different studies examining it. This may partly be due to the fact that knowledge is often assessed in a declarative way in these studies, instead of looking at knowledge-in-use (i.e. applying that knowledge to solve a problem in a meaningful way instead of simply stating that knowledge). This working paper thus argues for moving from climate and energy knowledge towards climate and energy literacy, with literacy involving knowledge, skills, and attitudes. With a climate and energy literacy perspective, as well as existing frameworks for how energy-related behavior can be modelled and explained, it theorizes how individual climate-friendly behavior can lead to collective action regarding energy transitions. As knowledge transfer and capacity building play a big role when scaling local solutions to a global level, the discussion paper advocates for concentrated efforts in interdisciplinary capacity building and lays out potential directions for future research.
Keywords: 330; energy transitions; education; knowledge transfer; capacity building